Investigation of Maritime Accidents’ Communication Management; Impact on the Post-Accident Operation Of The Shipping Companies Involved: Case Studies Presented - Giziakis, Konstantinos; Bountri, Konstantina (SPOUDAI Journal of Economics and Business, 2013)
The crisis management of a naval accident is a crucial matter that concerns many maritime companies (enterprises) due to the fact that such an accident can have significant repercussions on the company (and on Society in general). Having taken into consideration the effect that Media have on the formulation of the public opinion, it is clear that the way a Company deals with such crisis management is of the outmost importance and essentially defines the “sport”. In this work, the best available techniques and practices are analyzed towards the optimum management of a crisis accident; on a first and foremost level beforehand and secondly after the accident has taken place, on this very crucial next step where the climax and high point of this crisis is the accident itself. Next steps include the intensive analysis of three recent accidents: the Costa Concordia, Rena and Sea Diamond accidents. All three faced a brutal media assault and one way or another managed to survive or even move on almost unscathed. These case studies are examined from their handling aspect of the crisis that occurred and hit their company. In conclusion, it is clearly shown how vital it is for Maritime Companies to have an organized coherent plan of action/crisis management in conjunction with an open, direct and responsible stance towards the parties involved and hurt in an accident. JEL Classification: H12